Observations of diffuse radio emission in the Perseus Galaxy Cluster - Mungwariri, Clemence (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2020)
In this thesis we analysed Westerbork observations of the Perseus Galaxy Cluster at 1380 MHz. Observations consist of two different pointings, covering a total of âˆ¼ 0.5 square degrees, one including the known mini halo and the source 3C 84, the other centred on the source 3C 83.1 B. We obtained images with 83 Î¼Jy beamâ »Â¹ and 240 Î¼Jy beamâ »Â¹ noise rms for the two pointings respectively. We achieved a 60000 : 1 dynamic range in the image containing the bright 3C 84 source. We imaged the mini halo surrounding 3C 84 at high sensitivity, measuring its diameter to be âˆ¼140 kpc and its power 4 x 10Â²â ´ W Hzâ »Â¹. Its morphology agrees quite well with that observed at 240 MHz (e.g. Gendron-Marsolais et al., 2017). We measured the flux density of 3C 84 to be 20.5 Â± 0.4 Jy at the 2007 epoch, consistent with a factor of âˆ¼2 increase since the 1960s.
Keywords: Galaxies -- Clusters; Radio sources (Astronomy); Radio interferometers; Perseus Galaxy Cluster; Diffuse radio emission